Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pasien Rawat Inap RSUD Kanjuruhan Kepanjen Dengan Kepuasan Sebagai Variabel Intervening - Bagus Tuhu Hidayat; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe objectives of this study are 1) to know and analyze the impact of services quality to patient loyalty of hospital in region unit of Kanjuruhan Kepanjen. 2) To know and analyze the impact of services quality to patient satisfaction in the hospital as the intervening variable. 3) To know and analyze the impact of patient satisfaction to patient loyalty in the hospital. This is quantitative research and using survey to collect the data. The samples are taken by using purposive sampling with total 82 respondents.The result of this study showed that: 1) The services quality took effect positively and significantly to patient loyalty in the hospital of Kanjuruhan Kepanjen  region unit. 2) The positive and significant quality was taken effect to the patient satisfaction in the hospital. 3) The patient satisfaction was taken effect positively and significantly to patient loyalty in the hospital. Keywords: Services Quality, Patient Satisfaction, and Patient Loyalty